2013
DOI: 10.5897/jene12.045
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and abundance of small mammals in Chebera-Churchura National Park, Ethiopia

Abstract: In this study, we investigated species composition and abundance of small mammals (rodents and insectivores) in the recently established Chebera Churchura National Park, in Ethiopia between 2010 and 2011. Two study grids were established in seven selected habitats. In each grid, forty-nine Sherman live traps were used to capture the small mammals. A total of 704 individuals were captured in 5488 trap-nights. Among them, 682 (98.3%) were rodents and 12 (1.7%) were insectivores. These comprised 16 species of rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
2
18
3
Order By: Relevance
“…Relative abundance of small mammal species from six habitats This result goes in line with the study of Datiko and Bekele (2014) and Loggins et al (2019). The presence of diverse vegetation types in wooded grassland habitat could support higher number of species and individuals due to the presence of sufficient feeding and sheltering sites.…”
Section: Ta B L Esupporting
confidence: 85%
“…Relative abundance of small mammal species from six habitats This result goes in line with the study of Datiko and Bekele (2014) and Loggins et al (2019). The presence of diverse vegetation types in wooded grassland habitat could support higher number of species and individuals due to the presence of sufficient feeding and sheltering sites.…”
Section: Ta B L Esupporting
confidence: 85%
“…This pattern of distribution shows that the species is adapted to diverse ecological situations. Different studies in various parts of Ethiopia (Datiko & Bekele, 2013;Kostin et al, 2020) also reported the generalist behaviour of this species. A widespread distribution of M. natalensis is also reported in Ethiopia, on the northwestern plateau and south of the Ethiopian Rift Valley (Kostin et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have been conducted on rodent species richness and distribution in Ethiopia including Chilalo‐Galama Mountain Ranges (Kasso et al, 2010), the Simien Mountains National Park (Yihune & Bekele, 2012), Kaka and Hunkolo, Southeast Ethiopia (Girma et al, 2012), Chebera Churchura National Park (Datiko & Bekele, 2013), Awi Zone (Bantihun & Bekele, 2015), Bale Mountains National Park (Fekadu et al, 2015) and Choke Mountain (Simeneh, 2016). Most previous studies on rodent populations targeted the protected southwestern forests, south and southeastern highlands (Chekol et al, 2012; Habtamu & Bekele, 2008; Kasso & Bekele, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Adult and sub-adult groups had higher population size during the dry season than the wet season while juveniles had higher population size during the wet season. This might be due to the correlation between rainfall and the breeding patterns of for the majority of tropical small mammals (Happold, 1979;Datiko and Bekele, 2013), with most of the small mammals' species taking advantage of the availability of food and dense vegetation cover during the wet season to produce many offspring.…”
Section: Age Structure and Temporal Variationmentioning
confidence: 99%